Evolutionary-shaped goal orientation in Homo sapiens: how life sciences contribute to a better understanding of salespeople as knowledge brokers - Verbeke, Willem J.M.I.; Masih, Jolly (The Journal of personal selling & sales management, 2020)
Life sciences uses the Latin name Homo sapiens to describe humans, an animal species. First, we discuss how "popular beliefs" about the brain have inhibited the progress of life science applications in the field of selling. Subsequently, we present the Tinbergen's evolutionary perspective of life sciences and use "ultimate" and "proximate" explanations to understand the salesperson's main goal of becoming a knowledge broker. First, an ultimate explanation describes how the Homo sapiens evolved to acquire a big brain through natural selection processes, which led to the emergence of multiple cultures. This evoked a runaway selection of genes affecting brain functioning called "cultural drive hypothesis." The big brain shapes people's goal orientation and leads to better cooperation and exact copying of knowledge. Both are constitutive for the exponential emergence of innovations within and across cultures through multiple generations. Second, the proximate view explains how, for example, neural-endocrine mechanisms modulate knowledge brokering. We explore five hard-wired processes associated with a salesperson's skill in knowledge brokering, applying factual insights obtained from neuroscience, endocrinology, and genetics. Finally, we outline different strategies that researchers who seek to make new contributions to the field can undertake in doing research on selling.